Methods to improve quality of life, beyond medicines. Position statement of the European Academy of Dermatology and Venereology Task Force on Quality of Life and Patient Oriented Outcomes. (23rd October 2020) - Finlay, A.Y.; Chernyshov, P.V.; Tomas Aragones, L.; Bewley, A.; Svensson, A.; Manolache, L.; Marron, S.; Suru, A.; Sampogna, F.; Salek, M.S.; Poot, F.
Abstract: The pharmaceutical approach to skin disease has been hugely successful, but despite effective drugs being available and used, there are still vast numbers of people who continue to have some level of persisting skin disease and continue to experience quality of life (QoL) impairment. So the question that needs to be answered, while we await further advances in our drug‐based armamentarium, is how can we improve patients' QoL, beyond drugs? A working group was formed from members of the EADV Task Force on QoL and Patient Oriented Outcomes. Participants were asked to suggest all the ways in which they considered patients' QoL may be improved beyond medicines. Four groups of management approaches that may improve QoL in dermatology were identified: interventions within the dermatology service (hospitalization, multidisciplinary teams, patch testing and establishing relevant allergens and education), external services (corrective make‐up, climatotherapy and balneotherapy), psychological (psychological intervention, cognitive therapy, hypnosis), lifestyle (lifestyle behavioural changes, religion and spirituality and music). The ultimate aim of therapy is to eradicate a disease in an individual and return the person's life to normal. But until the day comes when this has been achieved for every skin disease and for every patient there will be a need to support and assist many patients in additional non‐pharmaceutical ways. These 'adjuvant' approaches receive too little attention while dermatologists and researchers strive for better pharmacological therapy. The different ways in which patients may benefit have been reviewed in our paper, but the reality is that most have a very poor evidence base. The research challenges that we have to meet are to identify those approaches that might be of value and to provide evidence for their optimal use. In the meantime, clinicians should consider the use of these approaches where QoL remains impaired despite optimal use of standard therapy.